Long cold winter - Perillo, Francesca (Mad Cave Studios, LLC, 2025)
In the not-too-distant future, the air on Earth has become unbreathable. However, a multinational company called Air Co. has constructed generators that provide oxygen for those who can afford it. Peace Dog, a desperate ex-soldier, who has been willing to do anything to obtain breathable air is haunted by his past and hunted by bounty hunters, though, he may have found a way out of his current predicament by helping a mysterious robot child escape the dangerous and congested city. But, someone from his past has no intention of letting him leave...alive.